Further clarification on not submitting bank guarantee upon advance payment for BRACU new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the clarification on not submitting bank guarantee upon advance payment for BRACU new campus project.